Prevalence and predictors of coronaphobia among frontline hospital and public health nurses - Labrague, Leodoro J.; De Los Santos, Janet Alexis A. (Public health Nursing, 2021)
Objectives To determine the prevalence as well as the predictors of coronaphobia in frontline hospital and public health nurses. Design This study used a cross‐sectional research study involving 736 nurses working in COVID‐19 designated hospitals and health units in Region 8, Philippines. Four structured self‐report scales were used, including the Coronavirus Anxiety Scale, the Brief Resilience Scale, the Perceived Social Support Questionnaire, and the single‐item measure for perceived health. Results The prevalence of coronaphobia was 54.76% (n = 402): 37.04% (n = 130) in hospital nurses and 70.91% (n = 273) in public health nurses. Additionally, nurses' gender (β = 0.148, p < .001), marital status (β = 0.124, p < .001), job status (β = 0.138, p < .001), and personal resilience (β = −0.167, p = .002) were identified as predictors of COVID‐19 anxiety. A small proportion of nurses were willing (19.94%, n = 70) and fully prepared (9.40%, n = 33) to manage and care for coronavirus patients. Conclusion Coronaphobia is prevalent among frontline Filipino nurses, particularly among public health nurses. Interventions to address coronaphobia among frontline nurses in the hospital and community should consider the predictors identified. By increasing personal resilience in nurses through theoretically driven intervention, coronaphobia may be alleviated.